Profil Nilai Laju Endap Darah (Led) Pada Pasien Tuberkulosis Dewasa Di Rsud Waled Periode 2022-2023 - APRILANINGTYAS, NUR ADILA; NOVIANI, ISTI; SEDAYU (Hang Tuah Medical Journal, 2025)
Background: Tuberculosis (TB) is an infectious illness directly caused by Mycobacterium tuberculosis. Primarily, they impact the lungs (pulmonary tuberculosis), but they can also include other bodily organs (extrapulmonary tuberculosis). The erythrocyte sedimentation rate (ESR) test is a standard blood examination. The erythrocyte sedimentation rate measures the sedimentation velocity of erythrocytes in unclotted blood, expressed in mm/hour. During acute inflammation and infections, both acute and chronic, the erythrocyte sedimentation rate (ESR) may rise over its usual range. Objective: To acquire a comprehensive understanding of the erythrocyte sedimentation rate (ESR) in adult tuberculosis patients throughout Cirebon Regency. Methods: This study is a descriptive observational analysis carried out at Waled Hospital in Cirebon Regency. A research sample of 148 patients was acquired by complete sampling methodology utilizing secondary data from medical records. The data underwent univariate analysis. Results: Univariate analysis revealed that among 145 tuberculosis patients aged ≥18 years, 85 (58.6%) were male, whereas 60 (41.4%) were female. Out of 145 TB patients, 137 (94.5%) had pulmonary TB, while 8 (5.5%) had extrapulmonary TB. Additionally, 133 patients (91.7%) exhibited an elevation in erythrocyte sedimentation rate (ESR), with a minimum value of 4 mm/hour and a maximum of 140 mm/hour. Conclusion: Tuberculosis cases in individuals aged 18 years and older are predominantly male, with the highest incidence being pulmonary tuberculosis and an elevation in erythrocyte sedimentation rate (ESR).